Active Layer Thickness Variation on the Qinghai‐Tibetan Plateau: Historical and Projected Trends. Issue 23 (8th December 2021) - Xu, Xiaoming; Wu, Qingbai
Abstract: As the buffer layer between the atmosphere and permafrost, the active layer is vulnerable to climate change. The variation in the active layer thickness (ALT) has important effects on surface energy balance, ecosystem, hydrological cycle, vegetation cover, and engineering construction in permafrost regions. The goal of this study is to discuss the active layer variation under different shared socioeconomic pathways (SSPs) for specific warming levels and to reveal the potential interactions between the ALT and the associated driving factors in typical hydrological basins. We revised the Stefan solution using the edaphic factor and the thawing index calculated by multimodel data from the Coupled Model Intercomparison Project Phase 6 to estimate the variation in the ALT. During 2015 to 2100, the ALT will increase by 14 cm (SSP1‐2.6), 43 cm (SSP2‐4.5), and 1.44 m (SSP5‐8.5), with average increase rates of 2.5 cm/decade, 5.8 cm/decade, and 17.5 cm/decade, respectively. The rates of increase of the ALT in the Hexi basin, Inner basin, Mekong basin, Yangtze basin, and Yellow basin are 12.6 cm/decade, 6.7 cm/decade, 5.2 cm/decade, 8.0 cm/decade, and 5 cm/decade, respectively. These results illustrate that air temperature is the primary determinant of ALT variation and normalized difference vegetation index (NDVI) and snow depth may influence the ALT change. The most significant correlations are between the ALT and NDVI in the Yangtze basin. In different seasons, the spring snow depth has the greatest impact on the ALT in the Hexi basin. Key Points: The modified Stefan solution was used to estimate the active layer thickness (ALT) variation in typical hydrological basins under different shared socioeconomic pathways The ALT exhibits an increasing trend in the Hexi, Inner, Mekong, Yangtze, and Yellow basins, but the trends are spatially heterogeneous Changes in air temperature have stronger control on the ALT than precipitation, snow depth, and normalized difference vegetation index